Coins and Winckelmann. Winckelmann and coins - Burnett, Andrew M. 1952- (2021)
Johann Joachim Winckelmann collected coins and cited them extensively in his History of Ancient Art and other works. An analysis of his use of them shows that, although he had a good knowledge of them and the relevant literature, he regarded them as being of less importance than the other arts. Nevertheless, his interest inaugurated a new art historical approach to the study of ancient coinage, which was adopted or modified by later important numismatists, such as Joseph Eckhel in Vienna in the eighteenth century and Barclay Head in London in the nineteenth century. Consequently, his views were very influential on the subject, having an impact for some two hundred years, until the middle of the twentieth century.
Keywords: Winckelmann, Johann Joachim -- 1717-1768; Winckelmann, Johann Joachim -- 1717-1768 -- Geschichte der Kunst des Alterthums; Sammlung; Münze; Antike